2018
DOI: 10.3390/fluids3020032
|View full text |Cite
|
Sign up to set email alerts
|

Submesoscale Turbulence over a Topographic Slope

Abstract: Abstract:Regions of the ocean near continental slopes are linked to significant vertical velocities caused by advection over a sloping bottom, frictional processes and diffusion. Oceanic motions at submesoscales are also characterized by enhanced vertical velocities, as compared to mesoscale motions, due to greater contributions from ageostrophic flows. These enhanced vertical velocities can make an important contribution to turbulent fluxes. Sloping topography may also induce large-scale potential vorticity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The modeled eddy‐induced heat and salt transport may be underestimated in our study. The horizontal resolution (10 km) of this model could resolve mesoscale eddy, but ignore the submesoscales (<10 km), such as topographic waves (Clément et al., 2016), and submesoscale eddies (Lazar et al., 2018; Su et al., 2018), etc. This may reduce the nonlinear effects on the heat/salt transport.…”
Section: Discussionmentioning
confidence: 99%
“…The modeled eddy‐induced heat and salt transport may be underestimated in our study. The horizontal resolution (10 km) of this model could resolve mesoscale eddy, but ignore the submesoscales (<10 km), such as topographic waves (Clément et al., 2016), and submesoscale eddies (Lazar et al., 2018; Su et al., 2018), etc. This may reduce the nonlinear effects on the heat/salt transport.…”
Section: Discussionmentioning
confidence: 99%
“…Irregularities in bottom topography play a pivotal role in the dynamics of the ocean's circulation (Marshall 1995;Gille, Metzger & Tokmakian 2004). It has been shown that oceanic mesoscale eddies and ubiquitous multiple alternating jets form and exhibit significant variability localised over topographic features (Thompson & Richards 2011;Boland et al 2012;Chen, Kamenkovich & Berloff 2015;Stern, Nadeau & Holland 2015;Khatri & Berloff 2018;Lazar, Zhang & Thompson 2018;Khatri & Berloff 2019). This variation in oceanic flows and flow-topographic interactions affect many processes such as the eddy-induced transport, eddy energetics and ocean ventilation (Thompson 2010;Abernathey & Cessi 2014;Barthel et al 2017;Tamsitt 2017;Youngs et al 2017;Klocker 2018).…”
Section: Introductionmentioning
confidence: 99%